Análisis Destinación Del Ingreso Impuestos De Industria Y Comercio En El Municipio De Cértegui – Chocó (2023)
There is no municipal tax numbers, among them is the industry and commerce tax income, said income is free destination. The collection of the income of the industry and commerce tax is paid by the taxpayers. Which constitutes a source of economic income for the municipalities, assists in the maintenance and operation of local public administrations.